Хүний бие махбодтой холбоотой цөөн үгийг алтай хэлний хүрээнд харьцуулан шинжих нь : The comparative study of some expression words which related to human body parts within the framework of Altaic languages - Арц (Mongolian Studies, 2023)
ххх